2014
DOI: 10.1371/journal.pone.0103552
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric HIV-1 Integrase Inhibitor BI-D Affects Virion Maturation but Does Not Influence Packaging of a Functional RNA Genome

Abstract: The viral integrase (IN) is an essential protein for HIV-1 replication. IN inserts the viral dsDNA into the host chromosome, thereby aided by the cellular co-factor LEDGF/p75. Recently a new class of integrase inhibitors was described: allosteric IN inhibitors (ALLINIs). Although designed to interfere with the IN-LEDGF/p75 interaction to block HIV DNA integration during the early phase of HIV-1 replication, the major impact was surprisingly found on the process of virus maturation during the late phase, causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
(78 reference statements)
2
29
0
Order By: Relevance
“…Allosteric IN inhibitors (ALLINIs, which are also known as LEDGINs, NCINIs or INLAIs) have recently emerged as a promising class of antiretroviral agents and select compounds are currently in clinical trials (Christ et al, 2010; Fader et al, 2014; Gupta et al, 2014; Kessl et al, 2012; Le Rouzic et al, 2013; van Bel et al, 2014). ALLINIs bind at the IN catalytic core domain (CCD) dimer interface and induce aberrant IN multimerization.…”
Section: Introductionmentioning
confidence: 99%
“…Allosteric IN inhibitors (ALLINIs, which are also known as LEDGINs, NCINIs or INLAIs) have recently emerged as a promising class of antiretroviral agents and select compounds are currently in clinical trials (Christ et al, 2010; Fader et al, 2014; Gupta et al, 2014; Kessl et al, 2012; Le Rouzic et al, 2013; van Bel et al, 2014). ALLINIs bind at the IN catalytic core domain (CCD) dimer interface and induce aberrant IN multimerization.…”
Section: Introductionmentioning
confidence: 99%
“…In these particles, the viral ribonucleoprotein complexes (vRNPs), mainly composed of the viral genomic RNA and NC, are eccentrically localized between the empty CA lattice and the viral membrane (7,9,17). A remarkably similar morphological defect is observed in particles generated in the presence of allosteric integrase inhibitors (ALLINIs) (also known as LEDGINs, NCINIs, or INLAIs) (18)(19)(20)(21)(22)(23). Proposed mechanisms that underlie this morphogenesis defect include ALLINI-induced aberrant IN multimerization (9,17,(24)(25)(26)(27) and inhibition of IN binding to the viral RNA genome (4).…”
mentioning
confidence: 95%
“…While a large fraction of eccentric particles contain irregularly shaped nonconical CA assemblies (9,17,24), they appear to retain all of the components necessary for reverse transcription, i.e., a dimeric viral RNA genome primed with tRNA-Lys, functional reverse transcriptase (RT) (23), and normal levels of NC-RNA complexes (4,17). Nevertheless, these particles are blocked at an early reverse transcription stage in target cells (9,11,13,24), the basis of which remains unknown.…”
mentioning
confidence: 99%
“…Investigating the molecular bases of the observed infectivity defects, we found that HIV-1 virions produced in the presence of the quinoline INLAI compound BI-D (developed by Boehringer Ingelheim) package normal levels of genomic RNA dimer and harbor a properly placed tRNA lys3 primer that could be extended ex vivo. In addition, reverse transcriptase extracted from these virions is fully active (21).…”
mentioning
confidence: 99%